2018
DOI: 10.4187/respcare.06283
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Use of Simple Exercise-Induced Bronchoconstriction Challenge Testing in Pediatric Exercise-Induced Dyspnea

Abstract: BACKGROUND: A simple exercise test to evaluate for exercise-induced bronchoconstriction (EIB) is routinely ordered in pediatric patients with exercise-induced dyspnea. However, the utility of this test in establishing the cause of exercise-induced dyspnea is not thoroughly examined in the pediatric population. We sought to assess the efficiency of a simple EIB challenge test in finding the cause of exercise-induced dyspnea in pediatric patients referred to our tertiary center in the last 5 y. METHODS: We perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…6 Many studies of pediatric patients referred for consultation for EID showed EIB in only 8% to 19%, in line with our findings. [1][2][3] Although most of our patients had been prescribed bronchodilators for suspected EIB, only 10% showed EIB on CPET results. This highlights that self-reported exercise-induced symptoms are poor predictors of EIB.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…6 Many studies of pediatric patients referred for consultation for EID showed EIB in only 8% to 19%, in line with our findings. [1][2][3] Although most of our patients had been prescribed bronchodilators for suspected EIB, only 10% showed EIB on CPET results. This highlights that self-reported exercise-induced symptoms are poor predictors of EIB.…”
mentioning
confidence: 85%
“…1,2 Previous studies show that EIB is present in just 8% to 19% of otherwise healthy children with EID. [1][2][3] In fact, most of these patients have 1 or more problems other than EIB limiting exercise. Cardiopulmonary exercise testing (CPET) can identify clinical entities that mimic EIB.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The search was further refined by selecting only those studies that contained one of the following key terms: "respiratory therapy," "protocols," "mechanical ventilation," "exacerbation," "bronchodilation," or "respiratory care." Nine manuscripts were identified from the search and were categorized as asthma diagnosis (1), asthma education (1), pressurized metered-dose inhaler (pMDI) instruction (2), RT-driven asthma protocols/management (2), and asthma treatment (3). These manuscripts and their findings are therefore discussed below.…”
Section: Methodsmentioning
confidence: 99%